Dilution of the Antarctic ozone hole into Southern midlatitudes. - Ajtic, Jelena (University of Canterbury. Physics and Astronomy, 2003)
Reduction in ozone levels in southern midlatitudes, caused by the transport of ozone-depleted air from the Antarctic polar vortex, is examined. The problem is approached from two different, but complementary, directions. First, a case study examining an atypical vertical profile of ozone in December 1998, caused by the presence of vortex air is presented. Second, the overall dilution effect in spring- and summer time in the years 1998, 1999, and 2000 is quantified. In the first approach, an ozonesonde profile over the Network for Detection of Stratospheric Change (NDSC) site at Lauder (45.0° S, 169.7° E), New Zealand, for 24 December 1998 showing atypically low ozone centred around 24 km altitude (600 K potential temperature), is analyzed. The origin of the anomaly is explained using reverse domain filling (RDF) calculations combined with a PV/O3 fitting technique applied to ozone measurements from the Polar Ozone and Aerosol Measurement (POAM) III instrument. The RDF calculations for two isentropic surfaces, 550 K and 600 K, show that ozone-poor air from the Antarctic polar vortex reached New Zealand on 24-26 December 1998. The vortex air on the 550 K isentrope originated in the ozone hole region, unlike the air on 600 K, where low ozone values were the result of dynamical effects. High-resolution ozone maps are generated, and their examination shows that the vortex remnant situated above New Zealand was the cause of the altered ozone profile on 24 December. The maps also illustrate mixing of the vortex filaments into southern midlatitudes, whereby the overall midlatitude ozone levels are decreased. In the second approach, to quantify the full impact of the dilution of the Antarctic ozone hole into southern midlatitudes in spring and summer of the years 1998, 1999 and 2000, diabatic RDF calculations are performed for parcels between 30° S and 60° S, initialized on a 1° longitude by 1° latitude grid, on seven potential temperature surfaces, between 400 K and 700 K. In each year, the trajectories are run back to ...